Pemanfaatan Aplikasi Paint Di TK Aisyiyah Bustanul Athfal Ar-Ridho Medan Amplas - Khaliza Marwah; Anggi Arysandi Hasibuan; Afrizan Tambunan; Fahmi Gunawan (Maslahah: Jurnal Pengabdian Masyarakat, 2020)
The purpose of this community service activity is to provide skills for the use of computer-based learning media, especially the use of the Paint application in Kindergarten Aisyiyah Bustanul Athfal Ar-Ridho Medan Amplas.Learning media are all things that teachers use to make it easier to deliver learning materials. The learning media studied are paint-based computer learning media applications that are used to stimulate children's cognitive abilities, especially in the aspects of learning and problem solving, logical thinking, and symbolic thinking. Keywords: Utilization, Paint Application,